2023
DOI: 10.2460/javma.23.01.0004
|View full text |Cite
|
Sign up to set email alerts
|

Cranial cruciate ligament disease is perceived to be prevalent and is misunderstood in field trial sport

Abstract: OBJECTIVE Cranial cruciate ligament disease (CCLD) is the most prevalent orthopedic problem in canines, affecting 3% to 5% of dogs, causing stifle instability, mobility dysfunction, and pain. The objective of this study was to evaluate the American Kennel Club field trial community’s knowledge of CCLD and estimate its perceived prevalence within this population. SAMPLE 401 field trial participants responded, with 701 field trial canines reported. METHODS A survey instrument was emailed to a population of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Male dogs neutered before 10 months and female dogs spayed before their first heat cycle had markedly higher reported rates of stifle injury compared to all other sex/neuter groups that had generally similar odds of stifle injury. There was a notable decrease in odds as handler age increased, with the highest odds of injury observed among dogs of the youngest handlers (18)(19)(20)(21)(22)(23)(24) and the lowest among dogs of handlers aged 65 years and older (OR: 0.35). For the teeter contact, dogs that were either not trained to perform a specific behavior at the end of the teeter or dogs…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male dogs neutered before 10 months and female dogs spayed before their first heat cycle had markedly higher reported rates of stifle injury compared to all other sex/neuter groups that had generally similar odds of stifle injury. There was a notable decrease in odds as handler age increased, with the highest odds of injury observed among dogs of the youngest handlers (18)(19)(20)(21)(22)(23)(24) and the lowest among dogs of handlers aged 65 years and older (OR: 0.35). For the teeter contact, dogs that were either not trained to perform a specific behavior at the end of the teeter or dogs…”
Section: Resultsmentioning
confidence: 99%
“…However, the complex etiology of CCL disease specifically makes it challenging to determine whether stifle injuries reported during training and competition were truly acute, traumatic injuries, or progression of previous chronic partial tears that were a result of other underlying risk factors. A study evaluating the cause of CCL injury in field trial dogs found owners to be inaccurate in their understanding of and assessment of how the injury occurs (i.e., traumatic vs. degenerative) ( 19 ). Therefore, we cannot say if any of the injuries reported were truly traumatic while actively participating during agility, or in fact whether they might have occurred regardless of the dog’s participation in agility activities.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the prevalence for complete CCL tears was high (86.7%) as the cases used in the study were identified because they had surgery for a CCL tear. The overall prevalence of CCL tears among all dogs has been reported to be between 3-5% which would lower the positive predictive value of this technique [2,27]. However, the specificity is unchanged by prevalence of the disease and the technique remains highly specific for complete CCL tear when identified.…”
Section: Plos Onementioning
confidence: 95%